Exogenous Calcium Alleviates Oxidative Stress Caused by Salt Stress in Peanut Seedling Roots by Regulating the Antioxidant Enzyme System and Flavonoid Biosynthesis - Yan Gao; Xuan Dong; Rongjin Wang; Fei Hao; Hui Zhang; Yongyong Zhang; Guolin Lin (MDPI AG, 2024)
Soil salinity is one of the adversity stresses plants face, and antioxidant defense mechanisms play an essential role in plant resistance. We investigated the effects of exogenous calcium on the antioxidant defense system in peanut seedling roots that are under salt stress by using indices including the transcriptome and absolute quantitative metabolome of flavonoids. Under salt stress conditions, the antioxidant defense capacity of enzymatic systems was weakened and the antioxidant capacity of the linked AsA-GSH cycle was effectively inhibited. In contrast, the ascorbate biosynthesis pathway and its upstream glycolysis metabolism pathway became active, which stimulated shikimate biosynthesis and the downstream phenylpropanoid metabolism pathway, resulting in an increased accumulation of flavonoids, which, as one of the antioxidants in the non-enzymatic system, provide hydroxyl radicals to scavenge the excess reactive oxygen species and maintain the plant's vital activities. However, the addition of exogenous calcium caused changes in the antioxidant defense system in the peanut root system. The activity of antioxidant enzymes and the antioxidant capacity of the AsA-GSH cycle were enhanced. Therefore, glycolysis and phenylpropanoid metabolism do not exert antioxidant function, and flavonoids were no longer synthesized. In addition, antioxidant enzymes and the AsA-GSH cycle showed a trade-off relationship with sugars and flavonoids.